Atuação e mise-en-scène no cinema brasileiro contemporâneo: o caso da trilogia cinza de Taciano Valério - Antonio Junior, Odécio (2019)
The studies we fetch to articulate deal with aspects related to the conduction of the mise-en-scène in the following movies made by director Taciano Valério: Onde Borges tudo vê (2011), Ferrolho (2012) and Pingo d' água (2014). It’s a case study that dialogs with cinema studies, acting theories and genetic critics. The observation of creative process of mise-en-scène considers the action of co-creative actors, a recurring practice at aesthetic experiments in brazilian contemporary cinema. The main concepts we discuss are "performance state" and "trigger", terms that cover elements theorized in the modus operandi build by the filmmaker along his career.